An evaluation of the effectiveness of the HIV/AIDS palliative care programme at Chris Hani Baragwanath Hospital - Leseka, Morero Elizabeth (University of Limpopo (Medunsa Campus), 2009)
Background: An understanding of the effectiveness of the hospital-based palliative care programme and the extent to which it changes the way patients are managed in the general medical wards is required, in order to develop evidence-based palliative care guidelines for Public Hospitals on the management of HIV/AIDS patients. Purpose: The study aimed to identify and describe the effectiveness of the Palliative Care programme on the management of HIV/AIDS patients at Chris Hani Baragwanath Hospital. The objectives of the study included to: • Determine the proportion of HIV positive patients admitted into Chris Hani Baragwanath general medical wards accessing services of a hospital-based palliative care team • Identify the care and support needs experienced by HIV positive patients • Compare the frequency of the met and unmet needs of HIV positive patients in those referred as opposed to those not referred to the hospital-based palliative care team Methods: Non-random quota sampling of 50 HIV positive patients confirmed by an ELISA test, and admitted with HIV related illnesses were selected from admission records of medical wards in Chris Hani Baragwanath Hospital. 8 (16%) of the patients were too ill to communicate, 12 (24%) declined the interview and 30 (60%) gave consent to be interviewed. The data was collected using researcher administered questionnaires, and captured on Microsoft Excel 2003. Descriptive statistics were analyzed using STATA 10. Participants were assessed for enrolment into the hospital-based palliative care programme, common palliative care needs experienced and the frequency of identification and provision of palliative care needs provided for patients in the medical wards with focus on physical symptoms, pain, psychosocial problems, integration of care and counselling needs. The group was further divided into those under a palliative care program and those not under palliative care, for further data analysis. Results: Findings revealed that very few patients (27%) with HIV&AIDS were accessing services of the hospital-based palliative care. Significant proportion (67%-77%) of HIV infected patients were experiencing physical symptoms, pain and psychosocial problems requiring palliative care interventions. Further findings revealed that for those participants who were not referred for the palliative care programme, symptoms and pain complaints were not effectively identified and treated by health personnel. Provision of psychosocial and spiritual support was inadequate and that the quality of life for HIV/AIDS patients was compromised due to lack of comprehensive and integrated holistic care. These components were found to be effectively addressed amongst the referred group. iv Conclusion and recommendations: Hospital-based palliative-care has limited effectiveness due to the small size of the team which is working against demands from increasing numbers of HIV positive patients. All health providers working in medical wards need to be trained in palliative care, to develop a capacity to integrate palliative care principles into the routine medical care of HIV/AIDS patients.
Thesis (MPH)--University of Limpopo, 2009.
Keywords: HIV/AIDS; Palliative care